Bankruptcy Analysis On Coal Mining Companies - Ramadhan, Yanuar; Laksono, Sherli Suci (Jurnal Riset Akuntansi dan Keuangan, 2021)
Financial distress is a condition in which the company is in an unhealthy state, but has not yet gone bankrupt. Therefore, it is important for companies to identify financial distress first as material for evaluation and early warning, especially since the world is currently experiencing an economic crisis due to the COVID-19 virus outbreak. This study aims to detect financial distress in coal mining sector companies. using the Altman Z-Score.The population used as research material was the Coal Mining Sector Company for the period 2016 - 2019. The sample technique used in this study was purposive sampling. The research sample was 22 companies in the coal mining sector with a research time of 4 years resulting in 88 samples. The data analysis technique used is descriptive analysis and logistic regression test using statistical test tools.Based on the testing of 5 (five) hypotheses, it is concluded as follows: Working Capital to Total Asset (WCTA), Retained Earning to Total Asset (RETA), Earning Before Interest and Tax to Total Asset (EBITTA), Market Value of Equity to Book Value of Liabilities (MVEBL), and Sales to Total Asset (STA) have no effect on financial distress